Growth With of Alfalfa Mutant in Different Nitrogen Fertilizer and Defoliation Intensity - Widyati Slamet; S. Sumarsono; S. Anwar; D.W. Widjajanto (Chemical Engineering Diponegoro University, 2012)
The research was conducted to evaluate growth of alfalfa mutan (plant height increment, number of leaves and dry matter production) in different Nitrogen Fertilizer and defoliation intensity. The design used was randomized block design 4x2 factorial with 3 replications. The first was dosage of Nitrogen fertilizerNitrogen (0, 30, 60 and 90 kg N / ha), the second factor was defoliation intensity (5 and 10 cm). Variables observed alfalfa growth (plant height increment, number of leaves, the production of dry matter (DM) forage). The results showed that different N fertilization did not affect the growth of alfalfa mutants. Defoliation intensity affectedmnumber of leaves and DM production of alfalfa mutant. Fertilization to 90 kg N / ha has not affected the growth and defoliation intensity 10 cm gave better growth on alfalfa mutant. [Keywords: alfalfa mutant; Nitrogen fertilizer; defoliation; growth]